EasyDCP: An affordable, high‐throughput tool to measure plant phenotypic traits in 3D. Issue 9 (14th June 2021) - Feldman, Alexander; Wang, Haozhou; Fukano, Yuya; Kato, Yoichiro; Ninomiya, Seishi; Guo, Wei
Abstract: High‐throughput 3D phenotyping is a rapidly emerging field that has widespread application for measurement of individual plants. Despite this, high‐throughput plant phenotyping is rarely used in ecological studies due to financial and logistical limitations. We introduce EasyDCP, a Python package for 3D phenotyping, which uses photogrammetry to automatically reconstruct 3D point clouds of individuals within populations of container plants and output phenotypic trait data. Here we give instructions for the imaging setup and the required hardware, which is minimal and do‐it‐yourself, and introduce the functionality and workflow of EasyDCP. We compared the performance of EasyDCP against a high‐end commercial laser scanner for the acquisition of plant height and projected leaf area. Both tools had strong correlations with ground truth measurement, and plant height measurements were more accurate using EasyDCP (plant height: EasyDCP r 2  = 0.96, Laser r 2  = 0.86; projected leaf area: EasyDCP r 2  = 0.96, Laser r 2  = 0.96). EasyDCP is an open‐source software tool to measure phenotypic traits of container plants with high‐throughput and low labour and financial costs. 概要: ハイスループットな3次元の表現型測定技術は急速に発展しており、植物の測定に広く応用されている。にもかかわらず、経済的なコストと手間が大きいため、ハイスループットの植物表現型解析が生態学研究に用いられることはほとんどなかった。 われわれは、画像解析技術を用いて大量の鉢植え植物個体の3次元点群を自動的に再構成し、形質データを出力するPythonパッケージ (EasyDCP) を開発・公開した。この論文では、撮影のためのセットアップと必要なハードウェアを最小限に抑えてDIYで行う方法を説明し、EasyDCPを行う一連の作業の流れと、有用性を紹介する。 本手法の性能を検証するために、手作業での測定結果、市販の高価格なレーザースキャナーでの測定結果と比較した。EasyDCPで推定された投影葉面積は、手作業での測定値と非常に高い相関があり (EasyDCP: r 2  = 0.96, laser scanner: r 2  = 0.96) 、植物の草丈に関してはレーザースキャナーよりも高い精度で形質を測定できた (Easy DCP: r 2  = 0.96, laser scanner: r 2  = 0.86)。 EasyDCPは, 鉢植え植物の表現型形質を, 高い処理能力と低い労力・金銭的コストで測定できるオープンソースのツールである。 摘要: 高通量植物三维表型是一个迅速崛起的领域, 在测量单株植物方面有着广泛的应用。尽管如此, 受到购买和使用成本的限制, 高通量植物三维表型很少用于生态研究领域。 我们开发了一个用于三维表型的Python工具EasyDCP, 其使用摄影测量技术自动重建盆栽实验植物的三维点云并输出表型参数。文中也指导了成像设置和所需硬件, 非常轻量且可DIY, 并且介绍了EasyDCP的功能和工作流程。 我们比较了EasyDCP与基于三维激光扫描的工业级植物表型设备在获取植物高度和植被覆盖度方面的表现。结果表明, 对于植被覆盖度, EasyDCP和三维激光扫描设备的测量和实测值都有很强的统计相关性 (EasyDCP: r 2  = 0.96, laser scanner: r 2  = 0.96) 。而对于高度, EasyDCP展示出更强的统计相关性 (Easy DCP: r 2  = 0.96, laser scanner: r 2  = 0.86)。 EasyDCP是一个测量盆栽实验植物三维表型参数的高通量、低劳动力和低成本的开源工具。